Диференційно-прогностична модель аналізу клінічного варіанту простої форми шизофренії - Мосейко, Олексій Валентинович; Moseyko, A.; Мосейко, А. В. (My University, 2017)
In order to develop a differential-prognostic model of schizophrenia in its simmlex atypical variants analysis which was based on the clinically-psychopathological research 100 patients who were suffering from the schizophrenia simplex were examined. On the basis of the analysis of clinical manifestations structure and dynamics, a differential-prognostic model that was based on the reflecting the evolution of the symptoms of the disease in the diagnostic process principle for each of 4 levels of atypical disease clinical picture was developed. The model includes the following stages: disease manifestation (the beginning of the diagnostic path); primary nosological qualification (primary determination of the nosological type of psychopathological disorders); the formation of a sub-syndromal hierarchy (the period of clinical observation of the developed disease clinical picture); syndromotropic consolidation (final nosological identification of psychopathological disorders); nosological shift (projection of the diagnostic path to the future). С целью разработки дифференциально-прогностической модели анализа психопатогенеза атипичных вариантов простой формы шизофрении в ходе клинико-психопатологического исследования было обследовано 100 пациентов, страдающих простой формой шизофрении. На основе данных анализа структуры и динамики клинических проявлений заболевания была разработана дифференциально-прогностическая модель, основанная на принципе отражения эволюции симптомов заболевания в диагностическом процессе для каждого из 4 уровней атипичности клинической картины заболевания. Модель включает следующие этапы: манифестация заболевания (начало диагностического пути); первичная нозологическая квалификация (первичное установление нозологической принадлежности психопатологических расстройств); становление субсиндромальной иерархии (период клинической обсервации развернутой клинической картины заболевания); синдромотропная консолидация (окончательная нозологическая идентификация психопатологических расстройств); нозологический шифт (проекция диагностического пути в будущее).
Differential-predictive model of analysis of schizophrenia simple clinical variants
Дифференциально-прогностическая модель анализа клинического варианта простой формы шизофрении
Keywords: schizophrenia; symptomatic; diagnostics; pathomorphosis; syndromokinesis; шизофрения; симптоматика; диагностика; патоморфоз; синдромокинез